2023
DOI: 10.3390/buildings13081886
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Museum Accessibility in High-Density Asian Cities: Case Studies from Seoul and Tokyo

Abstract: We investigated the relationship between urban accessibility of museums in the urban spaces of Tokyo and Seoul within limited travel distances. Similarities and differences were identified in the museum accessibility between the two cities. The urban accessibility of museums was set as the dependent variable, calculated via space syntax. For the spatial accessibility of museums, five walking ranges (1000–2000 m) were set as independent variables, with a distance of 250 m as the basic unit. Data normality and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…The higher the integration value, the higher the accessibility and commonality of the space [50]. Integration in space syntax is a primary indicator of spatial accessibility [51]. The integration of a line is, by definition, a value that indicates how integrated the line is with the system as a whole or how separate/inaccessible it is from the system [52].…”
Section: Space Syntaxmentioning
confidence: 99%
“…The higher the integration value, the higher the accessibility and commonality of the space [50]. Integration in space syntax is a primary indicator of spatial accessibility [51]. The integration of a line is, by definition, a value that indicates how integrated the line is with the system as a whole or how separate/inaccessible it is from the system [52].…”
Section: Space Syntaxmentioning
confidence: 99%
“…Depending on the form and method of analysis, convex spaces or axial lines are used to quantitatively analyze the use and perception of each convex space (axial line) based on the spatial depth generated while using the space [33]. In particular, studies have already been conducted to analyze urban space using axial lines to understand urban hierarchy and review spatial accessibility [34,35], and many scholars have demonstrated that social and economic phenomena occurring in urban spaces can be interpreted using indicators related to space syntax [36][37][38]. Integration is an important indicator that describes the accessibility of space in space syntax; it is divided into two scales: global and local integration.…”
Section: Space Syntaxmentioning
confidence: 99%
“…In space syntax, the standard value for interpreting intelligibility is usually 0.6. The closer it is to 1, the more recognizable the space, and the closer it is to 0, the less recognizable it is [37,39]. Equation ( 1) and Table 2 present the calculation and interpretation of the integration [33].…”
Section: Space Syntaxmentioning
confidence: 99%